Using strategy analytics for business value creation and competitive advantage - Kautish, Sandeep Kumar (IGI Global, 2024)
In the field of strategic management and business intelligence, a formidable challenge is present-conventional decision-making processes, heavily reliant on internal and external reports, struggle to meet the demands of this data-driven era. As organizations grapple with the increasing influx of data, the imperative for a strategic shift becomes undeniably apparent. Using Strategy Analytics for Business Value Creation and Competitive Advantage helps to guide leaders in extracting value, structuring complex problems, and crafting robust business strategies. Scholars and industry experts alike will find within the pages of this comprehensive guide a roadmap to navigate the intersection of organizational strategy and analytics, ultimately unlocking the key to business brilliance. Using Strategy Analytics for Business Value Creation and Competitive Advantage stands as a testament to the commitment to addressing the prevailing challenges in strategic decision-making. Tailored for researchers, academicians, industry experts, and scholars, the book delves into the intricacies of strategy analytics, offering transformative insights for those seeking a competitive edge in the evolving business landscape. Capturing the essence of this exploration, the transformative potential of strategy analytics is encapsulated in this valuable resource.